Porcine deltacoronavirus infection triggers mitophagy to dampen the interferon response and promote viral replication - Chen, Yue; Zhao, Yuan; Song, Qingqing; Zhang, Shijing; Zhu, Zhenbang; Wang, Wenqiang; Wen, Wei; Li, Xiangdong (Frontiers in Immunology, 2025)
Porcine deltacoronavirus (PDCoV) is a newly emerging enteric pathogenic that causes severe diarrhea in neonatal piglets worldwide and presents a significant public health threat due to its potential for cross-species transmission. MAVS (Mitochondrial Antiviral Signaling Protein), serves as a crucial immune hub that connects virus recognition (RIG-I/MDA5) and interferon response. In this study, we found that PDCoV infection damage mitochondrial structure and function, as shown by mitochondrial membrane potential depolarization and reduction in mitochondrial numbers. In addition, PDCoV infection triggered mitophagy to eliminate the impaired mitochondria and degradation of MAVS, which resulted in a suppression of Interferon type I (IFN-I) production, thereby promoting viral replication. In conclusion, the data of this study indicate that PDCoV can degrade MAVS through mitophagy to weak the production of IFN-I, thereby promoting virus replication.